The consolations of humor and other folklore essays - Oring, Elliott, author; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
An extensive examination of the role that jokes and humor have played in folklore tradition, these essays address many questions concerning humor using a theoretical framework.--Provided by publisher.
The consolations of humor -- Three Jewish jokes -- Whatever became of the dirty joke? -- Incongruous, appropriate, spurious -- Overlaps, oppositions, and ontologies -- Memetics and folkloristics: the theory -- Memetics and folkloristics: the applications -- Four laws of folklore -- To explain tradition.
Keywords: Wit and humor; Folklore